Inter-leg systolic blood pressure difference predicts cardiovascular events and mortality in incident hemodialysis patients. Issue 4 (April 2020) - Kato, Sawako; Lindholm, Bengt; Qureshi, Abdul Rashid; Mukai, Hideyuki; Yuzawa, Yukio; Maruyama, Shoichi
Background: High inter-arm blood pressure difference, a marker of vascular disease, may be difficult to assess in hemodialysis patients with arm arteriovenous fistulae. We investigated if high inter-leg systolic blood pressure difference associates with cardiovascular events and increased mortality in hemodialysis patients. Methods: Among 118 incident Japanese dialysis patients, bilateral leg blood pressure, arm blood pressure, brachial–ankle pulse wave velocity, and ankle–brachial index were measured, and the relative risk associated with inter-leg systolic blood pressure difference and other indices of vascular status was analyzed. Results: During follow-up (median, 46 months), 18 deaths and 75 cardiovascular events occurred in 38 patients. Kaplan–Meier curves showed that higher inter-leg systolic blood pressure difference was associated with overall (log-rank 9.35, p = 0.002) and cardiovascular (log-rank 5.81, p = 0.02) mortality. The period from the start of dialysis therapy to the first cardiovascular event was shorter as inter-leg systolic blood pressure difference increased (log-rank 23.7, p < 0.0001). In Cox hazard models, inter-leg systolic blood pressure difference greater than median independently predicted deaths (relative risk, 3.8; 95% confidence interval, 1.3–13.9) and cardiovascular events (relative risk, 3.9; 95% confidence interval, 1.9–9.21) after adjustments for age, sex, nutritional status, and diabetes, whereas other indices were not related to the risks. For well-nourished, moderately malnourished, and severely malnourished patients, the cumulative number of cardiovascular events in the high–inter-leg systolic blood pressure difference patients were 4.96, 31.44, and 55.18 events per 100 patient-years. Conclusions: Higher inter-leg systolic blood pressure difference associated with increased risk of mortality and cardiovascular events suggesting that wider application of inter-leg systolic blood pressure difference measurements may be warranted in hemodialysis patients.